Morbidity management and disability prevention for lymphatic filariasis in Sri Lanka: Current status and future prospects - Chandrasena, Nilmini; Premaratna, Ranjan; Gunaratna, Indeewarie. E.; de Silva, Nilanthi R. (PLOS Neglected Tropical Diseases, 2018)
Background Sri Lanka was acknowledged to have eliminated lymphatic filariasis (LF) as a public health problem in 2016, largely due to its success in Mass Drug Administration (MDA) to interrupt disease transmission. Analysis of the Strengths, Weaknesses, Opportunities and Threats (SWOT) of the national Morbidity Management and Disability Prevention (MMDP) program, the other pillar of the LF control program, was carried out with the objective of evaluating it and providing recommendations to optimize the use of available resources. Methodology A situation analysis of the MMDP activities provided by the state health sector was carried out using published records, in-depth interviews with key informants of the Anti Filariasis Campaign, site-visits to filariasis clinics with informal discussions with clinic workforce and personal communications to identify strengths and weaknesses; and opportunities to overcome weaknesses and perceived threats to the program were explored. The principal strength of the MMDP program was the filariasis clinics operational in most endemic districts of Sri Lanka, providing free health care and health education to clinic attendees. The weaknesses identified were the low accessibility of clinics, incomplete coverage of the endemic region and lack of facilities for rehabilitation. The perceived threats were diversion of staff and resources for control of other vector-borne infections, under-utilization of clinics and non-compliance with recommended treatment. Enhanced high level commitment for MMDP, wider publicity and referral systems, integration of MMDP with other disease management services and collaboration with welfare organizations and research groups were identified as opportunities to overcome weaknesses and challenges. Conclusions The recommended basic package of MMDP was functional in most of the LF-endemic region. The highlighted weaknesses and challenges, unless addressed, may threaten program sustainability. The identified opportunities for improvement of the programme could ensure better attainment of the goal of the MMDP program, namely access to basic care for all affected by lymphatic filarial disease.